2006 International Conference of the IEEE Engineering in Medicine and Biology Society 2006
DOI: 10.1109/iembs.2006.259563
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Cancer Stage from Free-text Histology Reports

Abstract: This article investigates the classification of a patient's lung cancer stage based on analysis of their free-text medical reports. The system uses natural language processing to transform the report text, including identification of UMLS terms and detection of negated findings. The transformed report is then classified using statistical machine learning techniques. A support vector machine is trained for each stage category based on word occurrences in a corpus of histology reports for pathologically staged p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 16 publications
0
33
0
2
Order By: Relevance
“…Wilcox and Hripcsak [7] assigned six different clinical conditions to narrative X-ray reports using different machine learning techniques. McCowan et al [8] infer the cancer stages from histology reports using statistical machine learning methods. Goldstein et al [9] compared information retrieval, machine learning and rule-based approaches for automatically assigning ICD-9 codes to radiology reports.…”
Section: Related Workmentioning
confidence: 99%
“…Wilcox and Hripcsak [7] assigned six different clinical conditions to narrative X-ray reports using different machine learning techniques. McCowan et al [8] infer the cancer stages from histology reports using statistical machine learning methods. Goldstein et al [9] compared information retrieval, machine learning and rule-based approaches for automatically assigning ICD-9 codes to radiology reports.…”
Section: Related Workmentioning
confidence: 99%
“…Iain McCowan [7] proposed techniques for pigeonholing of patient's lung carcinoma stage based on analysis of freetext medical reports. The approach uses natural language processing to transform the report text, UML [8] terms and espials of negated findings.…”
Section: A Review Of Related Workmentioning
confidence: 99%
“…At moment the system was applied on lung carcinoma because of data availability. Initial experiments were made to quantify system performance for T and N staging on a corpus of histology reports from more than 700 lung carcinoma patients [7]. At the sensitivity/PPV breakeven point, the system achieves average sensitivity of 0.61 and specificity of 0.88 for T staging and sensitivity of 0.78 and specificity of 0.90 for N staging.…”
Section: A Review Of Related Workmentioning
confidence: 99%
“…Studies have demonstrated some success in using natural language processing (NLP) systems to identify disease. As they become more reliable and widely available, the use of NLPs is likely to greatly enhance the value of text‐based messages (McCowan, Moore, and Fry 2006; McCowan et al 2007; Pakhomov et al 2007; Savova et al 2008).…”
Section: Expansion Areas For Linked Data Systemsmentioning
confidence: 99%